2018
DOI: 10.1016/j.healun.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenomapping and outcomes after heart transplantation

Abstract: Time-dependent precision phenotyping is a mechanistically insightful, data-driven approach to characterize patterns of clinical care and identify ways to improve clinical management and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…DCAF12 was previously implicated in several immunological processes in humans. In the peripheral blood, the decreased expression of DCAF12 (also known as WDR40A in clinical articles) precedes the onset of post-transplantation organ rejection [98,99]. Additionally, DCAF12 was associated with the development of intestinal Behçet's disease, chronic inflammatory disorder [100].…”
Section: Discussionmentioning
confidence: 99%
“…DCAF12 was previously implicated in several immunological processes in humans. In the peripheral blood, the decreased expression of DCAF12 (also known as WDR40A in clinical articles) precedes the onset of post-transplantation organ rejection [98,99]. Additionally, DCAF12 was associated with the development of intestinal Behçet's disease, chronic inflammatory disorder [100].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis of blood before and after hepatitis B vaccination showed that the level of DCAF12 in nonresponders was significantly upregulated after immunization [ 24 ]. In previous clinical studies, the decrease in DCAF12, also called WDR40A, in peripheral blood preceded organ rejection after organ transplantation [ 25 , 26 ]. DCAF12 is related to the development of intestinal Behçet's disease and chronic inflammatory diseases [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we performed intervariable clustering for patients. This dual-direction clustering yielded a color map of the results ( Figure 2 ), which visually represents the characteristics of the participants; this technique was recently named as “phenomapping.” 8 , 26 We applied this method to the data of the patient newly starting hemodialysis to assist our visual perception of individual patients. Moreover, the clustering may indicate similarities or redundancies among the clinical variables and provide an optimal method of variable reduction.…”
Section: Discussionmentioning
confidence: 99%